Introduction to android application development - Annuzzi, Joseph Jr.; Darcey, Lauren;Conder, Shane (Boston, Massachusetts : Addision-Wesley Publishing Company, 2016)
Introduction to Andoird application development, fifth edition, is the most useful real-world guide to building robust, commercial-grade Android apps with the new android 6 SDK, android studio and latest development best practices.
I. Platform Overview -- II. Application basics -- III. Application design essentials -- IV. Application design essentials -- V. Application delivery essentials -- VI. Appendixes.
Includes index.
Keywords: ANDROID (ELECTRONIC RESOURCE)